Reaction features of pump function of heart of wheelchair basketball players on the muscular loading depending on degree of loss of the lower limbs - Vakhitov, L.I. (2019)
In this article, the response of the heart rate and stroke volume of disabled athletes to the standard muscular load was studied. The athletes of the basketball team are divided into two groups. The first groups are wheelchair basketball players with amputated lower limbs. The second group is wheelchair basketball players with lower limb atrophy. A comparative analysis of heart rate and stroke volume was performed at rest and when performing a muscular load. It has been revealed that basketball players with amputated lower limbs have heart rate indicators at rest significantly higher, and ASW is lower than basketball players with atrophy of lower limbs. It has been established that in basketball players with amputated lower limbs when performing a muscular load, large changes occur on the part of the stroke blood volume and the values of the heart rate change to a lesser extent. Whereas, athletes with atrophy of the lower extremities when performing muscular load, there are large changes in the frequency of heartbeats and to a lesser extent the indices of stroke blood volume change.